1990
DOI: 10.7164/antibiotics.43.8
|View full text |Cite
|
Sign up to set email alerts
|

Eponemycin, a new antibiotic active against B16 melanoma. I. Production, isolation, structure and biological activity.

Abstract: Streptomyces hygroscopicus No. P247-7 1 (ATCC53709) produced a novel antibiotic eponemycin which exhibited specific in vivo antitumor effect against B 16 melanoma.Structural studies assigned {AS)-1 ,2-epoxy-2-hydroxymethyl-4-(7V-isooctanoyl-L-serylamino)-6-methylhept-6-ene-3-one to eponemycinwhichis unrelated to the knownantitumor antibiotics.In our continuing search for new microbial metabolites with antitumor activity, Streptomyces hygroscopicus No. P247-71 , isolated from a soil sample from the Philippines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 2 publications
0
55
0
2
Order By: Relevance
“…Although it cannot be ruled out that the apoptosis-inducing factor is distinct from the proteasome inhibitor, recent studies have shown that natural proteasome inhibitors have similar capacities to induce apoptosis in vitro and in vivo [32,39]. These compounds, small molecules with a peptide structure [21,27,42], which are produced and secreted by actinomycete species closely related to Nocardia [18,20,26], interfere with normal protein turnover in cells and can cause programmed cell death [47]. This proapoptotic activity may be due to extended longevity of caspases or modulation of expression of antiapoptotic Bcl-2, a regulator of the intrinsic apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although it cannot be ruled out that the apoptosis-inducing factor is distinct from the proteasome inhibitor, recent studies have shown that natural proteasome inhibitors have similar capacities to induce apoptosis in vitro and in vivo [32,39]. These compounds, small molecules with a peptide structure [21,27,42], which are produced and secreted by actinomycete species closely related to Nocardia [18,20,26], interfere with normal protein turnover in cells and can cause programmed cell death [47]. This proapoptotic activity may be due to extended longevity of caspases or modulation of expression of antiapoptotic Bcl-2, a regulator of the intrinsic apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, epoxomicin and eponemycin are members of a growing family of α′,β′-epoxyketone natural products having a linear peptide structure ( Fig. 2) (Koguchi et al, 1999(Koguchi et al, , 2000bSugawara et al, 1990;Tsuchiya et al, 1997). We reported the first total synthesis of epoxomicin , isolated from an unidentified actinomycete strain No.Q996-17, and showed that epoxomicin potently inhibits the 20S proteasome (Meng et al, 1999b) using an affinity reagent-labeled epoxomicin (Meng et al, 1999a;Sin et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Examples include epoxomicin (Hanada et al, 1992), eponemycin (Sugawara et al, 1990), lactacystin (Fenteany et al, 1995), TMC-95s (Koguchi et al, 2000a), phepropeptins (Sekizawa et al, 2001), and epigallocatechin-3-gallate (ECGC) (Nam et al, 2001). Among these, epoxomicin and eponemycin are members of a growing family of α′,β′-epoxyketone natural products having a linear peptide structure ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Eponemycin 1 is a potent peptide based cytotoxic agent, isolated in 1989 by Sugawara et al [1] from Streptomyces hygroscopicus (IC 50 ϭ 4 nM in B16 and 25 nM in L1210). Distinguishing features in this molecule are an unnatural γ,δ-dehydroleucine residue, an N-terminal lipophilic isooctanoic acid component, and a reactive C-terminal αЈ,βЈ-epoxy ketone motif.…”
Section: Introductionmentioning
confidence: 99%